Oxidative Halogenation of Sydnones Mediated by KX–Oxone System under Mild Conditions - Naveenkumar, S.; Mahagundappa, Maddani Rachappa (Synlett, 2025)
A direct, straightforward, and convenient approach for the synthesis of halogenated sydnones using the potassium halide (KX)–Oxone system via oxidative halogenation is developed. Highlights of the strategy include readily available chemicals, mild reaction conditions, short reaction time, excellent yields, and aqueous medium. Additionally, the scale-up reaction of the present halogenation indicated the practical feasibility on a higher scale under mild conditions.
Keywords: Oxidative halogenation; Synthetic methods; C–H functionalization; Sydnones; Scale-up